Protein Arginine Methyltransferase 5 Inhibition Upregulates Foxp3+ Regulatory T Cells Frequency and Function during the Ulcerative Colitis - Zheng, Yingxia; Huang, Liya; Ge, Wensong; Yang, Ming; Ma, Yanhui; Xie, Guohua; Wang, Weiwei; Bian, Bingxian; Li, Li; Nie, Hong; Shen, Lisong (Frontiers in Immunology, 2017)
Ulcerative colitis (UC) pathogenesis is related to imbalance of immune responses, and the equilibrium between inflammatory T cells and Foxp3+ regulatory T cells (Tregs) plays important role in the intestinal homeostasis. Protein arginine methyltransferases (PRMTs) regulate chromatin remodeling and gene expression. Here, we investigated whether inhibition of PRMTs affects colitis pathogenesis in mice and IBD patients and further explored the underlying mechanisms. In this study, we found that AMI-1(protein arginine N-methyltransferase inhibitor 1) treatments increased Tregs frequency, function and reduced colitis incidence. Adoptive transfer of AMI-1 treated Tregs could reduce the colitis incidence. Colitis was associated with increased local PRMT5 expression, which was inhibited by AMI-1 treatment. Additionally, PRMT5 knockdown T cells produced a better response to TGFb and promoted Tregs differentiation through decreased DNMT1 expression. PRMT5 also enhanced H3K27me3 and DNMT1 binding to Foxp3 promoter, which restricted Tregs differentiation. Furthermore, PRMT5 knockdown led to decreased Foxp3 promoter methylation during Tregs induction. PRMT5 expression had a negative relationship with Tregs in UC patients, knockdown of PRMT5 expression increased Tregs frequency and decreased TNFa, IL-6 and IL-13 levels. Our study outlines a novel regulation of PRMT5 on Tregs development and function. Strategies to decrease PRMT5 expression might have therapeutic potential to control ulcerative colitis.